2021
DOI: 10.1111/ele.13894
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties as key predictors of global grassland production: Have we overlooked micronutrients?

Abstract: Fertilisation experiments have demonstrated that nutrient availability is a key determinant of biomass production and carbon sequestration in grasslands. However, the influence of nutrients in explaining spatial variation in grassland biomass production has rarely been assessed. Using a global dataset comprising 72 sites on six continents, we investigated which of 16 soil factors that shape nutrient availability associate most strongly with variation in grassland aboveground biomass. Climate and N deposition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 72 publications
4
28
0
Order By: Relevance
“…To further demonstrate this, we used these seven variables to construct an SEM. This SEM was similar to Radujković et al (2021) final SEM but without composite variables, which showed that Fe and SOM had no significant direct effects on Biomass (Figure 1B). After removing these two paths from the model, we found that the SEM was significantly improved, with a lower AICc value (Figure 1C).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…To further demonstrate this, we used these seven variables to construct an SEM. This SEM was similar to Radujković et al (2021) final SEM but without composite variables, which showed that Fe and SOM had no significant direct effects on Biomass (Figure 1B). After removing these two paths from the model, we found that the SEM was significantly improved, with a lower AICc value (Figure 1C).…”
Section: Discussionsupporting
confidence: 69%
“…After removing these two paths from the model, we found that the SEM was significantly improved, with a lower AICc value (Figure 1C). These results indicate that the final SEM of Radujković et al (2021) is not the best model to explain the variation in grassland production. Finally, through model comparison and optimization (the R code is provided in the Supplementary Material), we obtained the best SEM to understand the key factors determining grassland production (Figure 1D).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations